The Impact of Social Media on Food Culture: A Comparative Analysis of Flavor, Tradition, and Identity in Thai and Indonesian Cuisines - Prastyo, Budy; Wisamitanan, Diyaporn; Kaewkong, Pittayatorn; Sasanapradit, Walaiporn (Journal of Buddhist Education and Research (JBER), 2025)
This study investigates how social media platforms such as Instagram, TikTok, and Facebook reshape culinary traditions and cultural identities in Thailand and Indonesia. Comparative analysis reveals differences in balancing traditional authenticity with digital innovation, highlighting both opportunities and challenges for culinary heritage preservation. This study explores how platforms like Instagram, TikTok, and Facebook transform food perception, consumption, and sharing in these two Southeast Asian nations. By comparing the role of social media in Thai and Indonesian food cultures, this paper examines how traditional flavors, culinary practices, and cultural identities are being preserved, adapted, and reimagined in the digital age. Through an analysis of viral food trends, influencer-driven content, and user-generated posts, the study highlights how social media has amplified the global appeal of iconic dishes like Thailand’s khanom buang (crispy crepes filled with sweet or savory meringue), and Indonesia’s Martabak, while also fostering new hybrid cuisines. The findings reveal that while both countries leverage social media to celebrate their rich culinary heritage, they differ in how they balance tradition and innovation. Ultimately, this study underscores the profound impact of social media on food culture, offering insights into how digital platforms are reshaping the culinary identities of Thailand and Indonesia in the 21st century.